Ionizing Radiation in Meat Processing and its Effects - Angeleska, Aleksandra; Uzunov, Risto; CHrcheva - nikolovska, Radmila; Dimitrieska Stojkovikj, Elizabeta; Esmerov, Igor; Angelovski, Ljupcho (VINČA INSTITUTE OF NUCLEAR SCIENCES, 2025)
From a historical perspective, even in ancient times there was an awareness of the connection between food and human health. Hippocrates (460 BC), the father of medicine, emphasized that many diseases could be linked to diet, highlighting the idea that “let food be thy medicine and medicine be thy food.” This early recognition of the importance of safe and high-quality nutrition laid the foundations for later efforts to preserve food and protect it from harmful influences. Over the centuries, various preservation methods were developed, ranging from drying, salting, and smoking to modern technologies that include ionizing radiation as an effective way of extending shelf life and maintaining the nutritional properties of meat. This paper provides a overview of ionizing radiation in meat processing. The advantages of this technology are evident in the elimination of pathogenic microorganisms, the extension of shelf life, and the preservation of nutritional properties, while acknowledging the limitations that may occur at higher doses. The analysis encompasses microbiological, chemical, physical, and sensory aspects, along with relevant regulatory frameworks at both international and national levels. It is concluded that ionizing radiation offers considerable potential for improving food safety and sustainability in the food industry, but requires careful application and transparent communication with consumers.